Transformative Potential of Culturally Responsive Teaching: Examining Preservice Teachers' Collaboration Practices Centering Refugee Youth - Amy Walker (MDPI AG, 2023)
Using a critical ethnographic approach, this research explores the experiences of preservice teachers in a Midwestern educator preparation program as they plan and implement an interdisciplinary community exploration and learning project using culturally responsive teaching practices to center local refugee youth. Data collection includes observing collaborative planning processes, collecting written reflections and photographs, and conducting post-project interviews. Findings suggest that culturally responsive teaching practices can lead to the development of asset-based mindsets of their peers through an emphasis on openness, interdisciplinary collaboration, and centering refugee youth. The implications of reframing service learning as learning and exploration are discussed, highlighting the benefits for both students and preservice teachers in terms of cultural competence and equity. Considerations for future research include the importance of longitudinal studies on the impact of cultural responsiveness in educator preparation programs. The research contributes to the understanding of effective teaching strategies for promoting equity in education and highlights the transformative potential of culturally responsive teaching on preservice teachers in collaboration with each other. Overall, engaging preservice teachers in community exploration and learning projects as culturally responsive teaching has the potential to dismantle racism, challenge biases, promote openness and partnership, and foster equity across middle-level learning spaces.